A PWM controlled quasi-resonant flyback converter for generating pulsed electric fields - (:unkn) unknown (My University, 2006)
Recently, a sterilization method of micro organism in food using pulse electric fields has been reported by many researchers. Treatment of the foods with the pulse electric fields (PEF) is an important technique to kill microorganisms and denature enzymes with only a small increase in temperature. Considering the application to the food industry, the energy efficiency of the method becomes important. High voltage pulsed electric fields can be used for pasteurization or sterilization of fluid foods. It is reported that microorganisms suspended in a solution were killed by the PEF process using a parallel plate electrode configuration. The new electrode configuration made is possible to raise the raise the energy efficiency for the pulsed sterilization process compared to that for conventional parallel-plate or concentric-cylinder electrode system. A proper insulation of the electrode surface is effective to increase the survival ratio reduction by applying lower voltage source. In this present study, a new modified PEF source with both narrow and wide pulses was designed to kill microorganisms. This modified PEF source is a power supply, which has a pulse width modulation (PWM) controlled quasi resonant flyback converter topology to generate pulsed electric fields. Converter topology can employ output transformer parasitic in the resonant tank, which makes it attractive for the high voltage switched mode power supply applications. A very broad range of operating frequency is required to control the output power. Therefore, the highly efficient PWM control technique in this resonant topology looks very promising. This PWM controlled quasi-resonant flyback converter topology combines the advantages of both resonant power conversion and pulse with modulation control techniques. Owing to operating high frequency using fast switching device MOSFET, this modified power supply is light and compact device. Adopting the inverter power supply with a microprocessor unit has been enabled by PWM control technique to generate pulsed electric fields. A PEF device was fabricated and waveforms were measured. Also good results are obtained from this converter with a microcontroller using cycle by cycle control.
Keywords: Microcontroller; Pulsed electric fields; PWM control; Quasi-resonant flyback converter; Zero voltage switching